TABLE SETTING IN THE INDONESIAN NAVY: FACILITATING LEARNING WITH VIDEOS - Munasita Munasita; Mustaji Mustaji; A. Mariono (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
This study is aimed to create a learning media that can improve studentâ€™s learning outcomes in the subject of â€œTable Mannerâ€ focusing on â€œTable Settingâ€. This study was applying â€œBorg and Gall research development modelâ€. The subject of this study was 65 Navy Enlisted trainees in Housekeeping. By treating a different way from a controlled class, a taped video containing subject matter was mainly delivered in an experimental class. And a posttest was conducted to clarify the final result of learning for both type of classes. It has been proven that posttest result of an experimental class has a higher mean than in a controlled class. Researcher believed that the use of video as a learning media boost trainees potential to achieve the learning outcomes. In other words, the developed product of learning video would potentially increase trainee understanding toward the subject matter.